1995
DOI: 10.1002/rcm.1290091216
|View full text |Cite
|
Sign up to set email alerts
|

Application of the fast‐evaporation sample preparation method for improving quantification of angiotensin II by matrix‐assisted laser desorption/ionization

Abstract: The fast-evaporation method of sample preparation has been applied for quantitative analysis using matrix-assisted laser desorption/ionization (MALDI) mass spectrometry. An instrumental protocol focusing on improvement of shot-to-shot repeatability and compensation for signal degradation has been developed for quantification of angiotensin II using the fast-evaporation technique and an internal standard. The fast-evaporation method was compared to the standard method of sample preparation (using a multicompone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
105
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(107 citation statements)
references
References 17 publications
2
105
0
Order By: Relevance
“…Here we employ the fast evaporation deposition method using nitrogen gas. The experiment was performed as reported previously [22]. It was found that the immobilized carbon nanotube matrix was not blown off during nitrogen gas spraying.…”
Section: The Advantage Of the Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here we employ the fast evaporation deposition method using nitrogen gas. The experiment was performed as reported previously [22]. It was found that the immobilized carbon nanotube matrix was not blown off during nitrogen gas spraying.…”
Section: The Advantage Of the Methodsmentioning
confidence: 99%
“…The sample solution, such as monosaccharides, disaccharides, ␣-CD and urine was deposited on the carbon nanotube layer and dried at ambient conditions. The fast evaporation method was performed as reported previously [22].…”
Section: Maldi Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…When crystallization is rapid (i.e. when the matrix is prepared in a volatile solvent and/ or the target is dried at elevated temperature and/or reduced pressure) the resulting crystals are small and crystallization of the analyte-matrix is much more uniform [2].…”
Section: A Review Of the Essential Features Of Maldi As They Relate Tmentioning
confidence: 99%
“…At the same time, several studies discuss the non-quantitative nature of MALDI-TOF MS (7, 8, 13, 19, 22, 26 -30). The main problem of MALDI is its poor reproducibility (sample to sample and shot to shot), which makes most quantitative measurements quite difficult at best (19,27,31). This is especially true for complex samples.…”
mentioning
confidence: 99%